PERSEPSI KEAGAMAAN MASYARAKAT TERHADAP SITUS PURBAKALA GUNUNG PADANG CIANJUR - Nanang Rustandi; Yusuf Wibisono (Tatar Pasundan: Jurnal Diklat Keagamaan, 2020)
Gunung Padang site, Cianjur District, a prehistoric cultural heritage becomes a concern because community activities also juxtaposed religious worships. The problems arise when various perception of the site’s existence is linked to myths. The focus is explored on how religious people related to the perception of Gunung Padang’s existence and restoration. This study uses qualitative research method using two data sources. The primary data are obtained from document studies, field observations, and in depth interviews. Secondary data are obtained from books, journals and other research documents. To analyze the relationship between community religious perceptions and culture of ancient sites, phenomenological approach is applied. The results indicate that religious perception over the site is strongly influenced by the process of integrating local religious and cultural understanding passed down for generations. The form of religious expressions are in form of belief, rite, and community. From the research findings, it arises a configuration of society’s religious perception towards Gunung Padang which integrates religion, culture, and belief (syncretism) characterized by local wisdom. Keywords: Religion; Culture; Society; Site; Myth